The division of the Iberian Peninsula in the light of the account by Pliny the Older - Antczak, Krzysztof (Studia Europaea Gnesnensia, 2012)
Pliny the Elder, a high ranking state official and a Roman scholar, the author of Naturalis Historia (NH), in the geographical books (III-VI) entitled situs, gentes, maria, oppida, portus, montes, flumina, mensurae, populi qui sunt aut fuerunt, presented the orbis terrarum universus - orbis Romanus, in other words pars nostra terrarum. The basis of the description of the world is provided by the locorum nuda nomina. Within this framework, the Encyclopaedist included the description of the Iberian Peninsula (Hispania); in more precise terms, it was made a part of the European periplus (books III-IV). The description of Spain is interspersed with remarks of etymological, ethnographic or geographical nature. In 197 BC, Spain underwent its first division into two provinces – the Nearer Hispania (provincia Hispania Citerior) and the Further Hispania (provincia Hispania Ulterior). The division persisted until the times of Augustus, when the conquest was completed and Roman administration in Hispania reorganised. Ultimately, the Iberian Peninsula was split into three provinces: Hispania Citerior Tarraconensis, Hispania Ulterior Baetica and Hispania Ulterior Lusitania. At present, there is some debate concerning the course of reorganisation of the Roman administration in Hispania under the first emperor. The matter concerns the stages – phases in which the three Roman provinces on the peninsula came into existence. The issue has been additionally complicated by Augustus’ edict of 15 BC, discovered in Spain in 1999, which mentions a provincia Transduriana. In the Indices of the geographical books, Pliny presented the units he would use as reference when describing orbis terrarum universus. With regard to Spain, he indicated that he would rely on the administrative division of Hispania which was valid in the latter half of the 1st century AD - Baetica, Nearer Hispania (Hispania Citerior) and Lusitania. At the same time he remarked that he would present the Atlantic coast of Nearer Spain and Lusitania according to the European periplus, i.e. in the final part of book IV. It has to be observed that first Pliny the Elder presented the current administrative division of the Iberian Peninsula for the latter half of the 1st century AD. The principal political-administrative narrative was skilfully supplemented with historical facts (which resulted from the previous assumptions - locorum nuda nomina and res, historiae et observationes). In doing so, he resorted to the sources at his disposal. To begin with, he based his narration of the up-to-date administrative sources, which allowed him to present the current administrative division of the peninsula. At the same time he did not fail to refer to earlier sources, for instance Agrippa’s work, as well as an inscription commemorating the successes of Pompey Magnus. Pliny’s account is characterised by a historical point of view. The Encyclopaedist subjected the above sources to a historical analysis. He attempted to enhance the description of the present state with information from the past. The facts extracted from those were provided with remarks of historical nature.